2018
DOI: 10.1007/s10549-018-4912-x
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant therapy for breast cancer treatment: an expert panel recommendation from the Brazilian Society of Breast Surgeons 2018

Abstract: This manuscript provides updated guidance according to the views of the SBM's experts for the clinical practice of breast cancer surgeons. This manuscript depicts the summarized recommendations for NAC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
5
0
1
Order By: Relevance
“…Corroborating the medical literature, the panel considered the biopsy of an N0 lymph node after the NAC a safe procedure. They also confirmed the safety of SLNB for initially N1 patients that became N0 after neoadjuvant treatment 15 . An analysis of the national cancer database demonstrated an increased number of SLNB in breast cancer patients with positive lymph node undergoing NAC between 2012 and 2015 16 .…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Corroborating the medical literature, the panel considered the biopsy of an N0 lymph node after the NAC a safe procedure. They also confirmed the safety of SLNB for initially N1 patients that became N0 after neoadjuvant treatment 15 . An analysis of the national cancer database demonstrated an increased number of SLNB in breast cancer patients with positive lymph node undergoing NAC between 2012 and 2015 16 .…”
Section: Discussionmentioning
confidence: 61%
“…These options include patients with clinically radiologic remission but not complete pathologic response. On the basis of the clinical data, the Brazilian Society of Mastology consensus recommends axillary dissection for patients diagnosed with micrometastasis in SLNB after neoadjuvant treatment, therefore, we were surprised that breast surgeons are omitting ALND for these patients 15 . The surgical approach to the axilla in breast cancer patients undergoing neoadjuvant therapy is still controversial, and more studies are needed to clarify the best axillary management after NAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the developing world, the incidence rate of breast cancer has been increasing due to extended life expectancies, developing urbanization, and the adoption of stressful modern lifestyles [3]. Surgery [4], chemotherapy [5], endocrinotherapy [6], molecular targeted therapy [7], and immunotherapy [8] are the primary anticancer treatments currently being utilized. However more and more studies have shown that these therapies are also associated with numerous postoperative complications, toxicities, and side effects, such as deep vein thrombosis (DVT) [9], upper limb edema [10], myelosuppression [11], liver and renal function, gastrointestinal tract reaction [12], cardiac damage [13], peripheral neurotoxicity, menopause like syndrome [14], or local radiation damage [15].…”
Section: Introductionmentioning
confidence: 99%
“…Embora haja discussão na literatura sobre a classificação mais adequada, o tipo basallike por vezes é nomeado equivocadamente de triplo-negativo (Aysola et al, 2013;Yao et al, 2017;Yeo e Guan, 2017;Barbosa et al, 2018). É importante esclarecer que o câncer de mama triplo negativo (triple-negative breast cancer -TNBC) é um termo baseado em ensaios clínicos de imunohistoquímica para receptor de estrógeno (ER), progesterona (PR) e HER2, enquanto o basal-like é um fenótipo molecular inicialmente definido usando microarrays de cDNA.…”
Section: Lista De Abreviaturas E Siglas 2hgunclassified